Missionary capitalist : Nelson Rockefeller in Venezuela - Rivas, Darlene (Luther Hartwell Hodges series on business, society, and the state., 2002)
This work draws on Nelson A. Rockefeller's personal papers and research in Latin American archives to detail Rockefeller's efforts to promote economic development in Latin America, particularly Venezuela, from the late 1930s through to the 1950s.